Protective effects of engineered Lactobacillus johnsonii expressing bovine granulocyte-macrophage colony-stimulating factor on bovine postpartum endometritis - Guo, Jing; Cao, Xu; Li, Zhiqiang; Wang, Caiyu; Zhong, Chengkun; Wang, Simin; Fan, Zhile; Zhao, Jing; Wang, Jun; Fang, Yi; Liu, Hongyu; Ding, He; et al. (Frontiers in Veterinary Science, 2024)
Postpartum endometritis is a common reproductive disorder in bovines which can lead to a prolonged open period, infertility and other complications. Lactobacillus strains have been shown to prevent these conditions by reducing inflammation levels in the uterus, but it may suffer from the limited applicability for the lack of direct antimicrobial action and longer treatment durations. In this study, we successfully constructed a recombinant Lactobacillus johnsonii strain expressing bovine Granulocyte-macrophage colony-stimulating factor (GM-CSF), which was found to significantly reduce inflammation levels induced by E. coli infection in the uterus. This was evidenced by reduced expression of inflammatory markers, including IL-6, IL-1β, and TNF-α, as well as decreased myeloperoxidase (MPO) activity and nitric oxide (NO) concentration. Histological examination also revealed improved uterine morphology and reduced pathological damage in mice treated with the engineered strain. Crucially, our results demonstrate that the recombinant L. johnsonii expressing GM-CSF exerts beneficial effects on bovine endometritis by reducing levels of inflammatory cytokines.Lactobacillus johnsonii strain expressing bovine GM-CSF in preventing inflammatory conditions in the postpartum uterus. The development of this strain could lead to novel and effective protective options for postpartum intrauterine inflammation-related disorders, ultimately improving bovine reproductive efficiency.